INFβ therapy for COVID-19: the new SNG001 drug - Holgate, Stephen (Henry Stewart Talks, 2020)
Why INFβ was chosen as a therapy for COVID-19, Previous use of INFβ by inhalation, Safety of INFβ as a therapy, SNG001 mode of delivery, SNG001 clinical trials and future prospects